Pembentukan Portofolio Optimal Saham Dengan Menggunakan Model Portofolio Mean-Variance-Skewness-Kurtosis - Gubu, La; Rashif Hilmi, Muhamad (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2024)
This paper presents the development of Markowitz's classic Mean-Variance (MV) portfolio model, namely the Mean-Variance-Skewness-Kurtosis (MVSK) portfolio model. The MVSK portfolio model aims to overcome the fact that most stock returns in the capital market do not follow a normal distribution, and there are skewness and excessive kurtosis. The solution of the MVSK portfolio model is determined using the Newton-Raphson method. To see the advantages of the MVSK model, an empirical study was carried out on a portfolio construction using the four best stocks on the Indonesian Stock Exchange, which are included in the LQ45 index group for February-July 2023. The empirical study shows that for risk aversion   the performance of portfolios formed using the MVSK model outperforms portfolios formed using the classical MV model, while for risk aversion   the performance of portfolios formed using the classic MV model outperforms portfolios formed using the MVSK model. In addition, it was also found that for risk aversion , the weight and performance of the portfolio formed using the MVSK model were close to the weight and performance of the portfolio formed using the classic MV model. Keywods: portofolio, return, risk, portfolio performance, MVSK.